Angioscopic differences of coronary intima between diffuse and focal coronary vasospasm: Comparison of optical coherence tomography findings. Issue 3 (September 2018) - Kitano, Daisuke; Takayama, Tadateru; Sudo, Mitsumasa; Kogo, Takaaki; Kojima, Keisuke; Akutsu, Naotaka; Nishida, Toshihiko; Haruta, Hironori; Fukamachi, Daisuke; Kawano, Taro; Kanai, Takashi; Hiro, Takafumi; et al.
Highlights: Coronary angioscopy visualized features of intima in coronary artery vasospasm. Focal coronary spasm is involved in atherosclerotic plaque containing lipid. In case of detecting focal coronary spasm, we should take care even if there are no significant coronary risks. Abstract: Background: Coronary artery vasospasm (CS) can be identified as either a diffuse type or focal type; however, the difference in endothelial characteristics between these spasm types remains unclear. The features of coronary intima associated with diffuse spasm and focal spasm using coronary angioscopy (CAS) were evaluated and the optical coherence tomography (OCT) findings were compared. Methods: CAS and/or OCT observational analysis was performed in 55 patients (mean age: 61.4 years, 31 men) who had acetylcholine-provoked CS (diffuse CS, 31 patients; focal CS, 24 patients). The yellowness of the intima, presence of thrombus in CAS, and intimal characteristics based on the OCT results were evaluated. Results: CAS showed more atherosclerotic yellow plaques at the focal spasm segment than at the diffuse spasm segment ( p  = 0.032). Moreover, there were more thrombi at the focal spasm segment ( p  = 0.039). In addition, OCT results revealed that the intima area, maximum intima thickness, and lipid content in the focal CS group were larger than the diffuse CS group (4.22 ± 1.67 mm 2 vs. 3.45 ± 2.36 mm 2 ; 0.71 ± 0.29 mm vs. 0.53 ± 0.30 mm; 55.9% vs. 32.0%, p  < 0.001, respectively). Conclusions: These results indicate that the presence of atherosclerotic plaques at the spasm site is likely to be related to the occurrence of a focal vasospasm. This may support the difference of features between focal CS and diffuse CS and contribute to precise treatment for each spasm type.